POLARIS (α UMi),- MULTISTELLAR SYSTEM IN THE OPEN CLUSTER - Usenko, I. A.; Miroshnichenko, A. S.; Klochkova, V. G.; Panchuk, V. E. (Одеські астрономічні публікації, 2007)
We present the results of our analysis of high-resolution spectroscopic observations of Cepheid α UMi (Polaris A) and main-sequence type stars Polaris B and HD 5914, - optical companion and a member of Polaris open cluster. The last ones are objects with high projected rotational velocities v sin i = 110 km s-1 and 100 km s-1, respectively. The derived atmosphere parameters are: Polaris A: Teff=6022 K; log g=2.2; Vt=4.3 km s-1; Polaris B: Teff=6900 K; log g=4.3; Vt=2.5 km s-1; HD 5914: Teff=8800 K; log g=4.0; Vt=2.0 km s-1. C, Na and Mg content in last two stars is close to solar, whereas Polaris A demonstrates its that is typical for Cepheid after the first dredge-up stage. The distances to Polaris B and HD 5914 are 109.5 and 108 pc, respectively. The RV pulsational amplitude of Polaris A decreased to 0.6 s-1 in 2005 and increased to 7.5 km s-1 in 2003